Immunolocalization of aquaporins 1 and 9 in the ram efferent ducts and epididymis - Schimming, B. C. [UNESP]; Pinheiro, P. F. F. [UNESP]; Matteis, R. de [UNESP]; Machado, C. M. [UNESP]; Domeniconi, R. F. [UNESP] (Blackwell Verlag GmbH, 2015)
Aquaporins (AQPs) are essential membrane protein channels for the transport of water across membranes. Fluid movement in the epididymis is important for modulation of the luminal environment, in which sperm mature and reside. This study was designed to understand the morphology and localization of AQPs in ram efferent ducts (ED) and epididymis. For this purpose, the epididymis of seven animals were removed for histologic and immunohistochemical analyses. AQP1 immunoreactivity was observed in the apex of the ED, and AQP9 was found adjacent to the nuclei of the epithelial cells of the ED. The epithelial lining of ram epididymis is pseudostratified columnar and presents principal, basal, apical and narrow cells. In the initial segment (IS), a moderate reaction for AQP1 was observed in the apical cytoplasm of epithelial cells. An intense reactivity for AQP1 was noted over the microvilli of principal cells and in spermatozoa in the caput. In the corpus and cauda, AQP1 was noted only over the endothelial cells of vascular channels located in intertubular spaces. A weak-to-moderate reaction for AQP9 was observed in the nuclei of epithelial cells in the IS, caput and corpus of the epididymis. In the cauda, an intense reaction to AQP9 was observed in the epithelial border. In the IS, caput and corpus, the reactivity for AQP9 differed from those observed in domestic animals. The cauda showed a pattern similar to that previously described. These results indicate that AQPs 1 and 9 have reversed locations and roles in rams, suggesting activity variations related with fluid and solute absorption throughout the epididymis.